Alternatives to liberal constitutional democracy - S. Law, David (2019)
The global appeal of liberal constitutional democracy—defined as a competitive multiparty system combined with governance within constitutional limits—cannot be taken for granted due to the existence of competing forms of government that appear successful along a number of practical dimensions and consequently enjoy high levels of public acceptance. Proponents of liberal constitutional democracy must be prepared to explain and defend its capacity to satisfy first-order political needs. A system of government is unlikely to command popular acceptance unless it can plausibly claim to address the problems of oppression, tribalism, and physical and economic security. Along these dimensions, the advantages of liberal constitutional democracy over the alternatives of social democracy of the type seen in Scandinavia, and bureaucratic authoritarianism of the type seen in parts of Asia, are not self-evident. Within Asia alone, functional alternatives to liberal constitutional democracy run the gamut from illiberal nondemocracy in China, to liberal one-party rule in Japan, to illiberal constitutional democracy in Singapore, to liberal constitutional nondemocracy in Hong Kong, to hereditary monarchy in Bhutan.